On Their Own Terms: Temperance in Southern Ontario’s Black Community (1830-1860) - Bridgen, Lorene (Ontario History)

(untitled) (The Ontario Historical Society, 2009)
This article examines the role of African Canadians in southern Ontario’s temperance movement and the extent to which temperance offered them freedom. It discusses African Canadians who drank, including the Reverend John Jackson and James T. Rapier, and the participation of key figures such as Henry Bibb, Mary Ann Shadd Cary, William Whipper and the Reverend Israel Campbell, who supported the cause of temperance by offering individual support, organizing voluntary reform and endorsing legal enforcement. Also analyzed are the contributions of Whites to African-Canadian temperance. It concludes that African Canadians played a more important role in the cause of temperance than previously known.